Assessment of Public Relations Strategies Adopted by the Nigeria Police in Its Image Management - Aondo Vivian; Gana Hope; Musa Mathias; Anthony I. Igyuve (Darul Yasin Al Sys, 2026)
This study examines public relations strategies adopted by the Nigeria Police Force (NPF) in managing its institutional image, with particular attention to how these strategies shape public perceptions and mitigate negative publicity. Using a descriptive survey design, questionnaires were distributed to a randomly selected sample of respondents through simple random sampling to assess the relationship between public relations practice and image management within the NPF. The findings indicate a significant positive impact of public relations strategies on improving the public image of the Nigeria Police Force, confirming that well-crafted and consistently implemented communication efforts contribute to enhanced public perception. At the same time, the study identifies persistent impediments that constrain the effectiveness of these strategies, including structural and operational challenges within the organization. The study concludes that prioritizing media relations, adopting a more strategic and evidence-informed approach to addressing the identified constraints, and conducting a comprehensive review of existing public relations strategies—grounded in open and transparent communication and stakeholder feedback—are critical for strengthening image management. These conclusions underscore the need for the Nigeria Police Force to institutionalize responsive, dialogic public relations practices as part of broader efforts to rebuild public trust.